2010
DOI: 10.1111/j.1600-9657.2010.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental injuries among children and adolescents aged 1–15 years attending to public hospital in Temuco, Chile

Abstract: A cross-sectional study was carried out in children and adolescents of both sexes, aged 1-15 years that sought dental emergency attention to the Regional Hospital between 2004 and 2007 in Temuco, Chile. The purpose of this study was to identify the aetiology, types of traumatic dental injuries in primary and permanent dentitions, sex and age distributions, accident location; and time elapsed before emergency treatment in children and adolescents. The sample consisted of 359 patients with 145 primary teeth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
95
5
38

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(179 citation statements)
references
References 40 publications
41
95
5
38
Order By: Relevance
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, school-aged boys are more prone to risky behavior, a lack of discipline, fi ghting and sports than school-aged girls. Th e fi ndings of our study indicated that injuries occurred most often in children aged 7-12, supporting the fi ndings of other authors 8,18,22 . Th e peak of injuries to primary teeth occurs at the age of 2 and at the age of 9 for permanent teeth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations